1986
DOI: 10.1128/aem.52.4.700-705.1986
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization by Campylobacter jejuni and Campylobacter coli

Abstract: An attempt was made to elucidate in Campylobacter spp. some of the physiologic characteristics that are reflected in the kinetics of CO2 formation from four '4C-labeled substrates. Campylobacterjejuni and C. coli were grown in a biphasic medium, and highly motile spiral cells were harvested at 12 h. Of the media evaluated for use in the metabolic tests, minimal essential medium without glutamine, diluted with an equal volume of potassium sodium phosphate buffer (pH 7.2), provided the greatest stability and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although the utilization of formate, L L-lactate, cysteine, glutamine, a-ketoglutarate, succinate, fumarate and aspartic acid and serine has been investigated by several studies (Alexander 1957;Kiggins and Plastridge 1958;Zemjanis and Hoyt 1960;Smibert 1963;Hoffman 1979;Veron et al 1981;Elharrif and Megraud 1986;Karmali et al 1986;Westfall et al 1986), the kinetic data of these substrates had not been determined. In the present study, kinetic data of individual substrate including affinity constant was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the utilization of formate, L L-lactate, cysteine, glutamine, a-ketoglutarate, succinate, fumarate and aspartic acid and serine has been investigated by several studies (Alexander 1957;Kiggins and Plastridge 1958;Zemjanis and Hoyt 1960;Smibert 1963;Hoffman 1979;Veron et al 1981;Elharrif and Megraud 1986;Karmali et al 1986;Westfall et al 1986), the kinetic data of these substrates had not been determined. In the present study, kinetic data of individual substrate including affinity constant was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of information impeded the full elucidation of survival, transmission and the pathogenicity of Campylobacter. Previous studies on Campylobacter metabolism (Alexander 1957; Kiggins and Plastridge 1958;Zemjanis and Hoyt 1960;Smibert 1963;Hoffman 1979;Veron et al 1981;Elharrif and Megraud 1986;Karmali et al 1986;Westfall et al 1986;Mendz et al 1997) were, mostly, based on investigation of substrate utilization in growth media and rarely derived kinetics data of these substrates studied. It was found that citric acid cycle (CAC) intermediates, but not carbohydrates, can serve as excellent energy source for Campylobacter (Alexander 1957).…”
Section: Introductionmentioning
confidence: 99%
“…As most strains of C. jejuni cannot utilise sugars [24,26,27], C. jejuni mainly relies on amino acids and C4-dicarboxylates as a primary energy source [28]. C. jejuni is known to preferentially use the amino acids aspartate, serine, glutamate, asparagine and proline [29][30][31][32], as well as the C4-dicarboxylates fumarate, succinate and malate [30]. Use of amino acids and C4-dicarboxylates for energy metabolism are interconnected as amino acids can be converted into C4-dicarboxylates that can enter the TCA cycle or be used in the electron transport chain for energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…However, concentrations of these electron acceptors typically are low within gut environments and it is unclear how much growth may be supported by this process. Campylobacter can conserve energy via substrate-level phosphorylation during catabolism of the amino acids aspartate, alanine, glutamate, glutamine, methionine and serine (Westfall et al 1986;Mohammed et al 2004;Velayudhan et al 2004). Intermediate and end products of amino acid catabolism by Campylobacter include acetate, formate, fumarate, lactate, pyruvate and succinate thus indicating the involvement of mixed acid fermentation and reductive metabolism of the tricarboxcylic acid pathway (Laanbroek et al 1978a;Mendz and Hazell 1996).…”
mentioning
confidence: 99%